Invasive treatment of persistent postoperative chylothorax secondary to thoracic duct variation injury: Two case reports and literature review. Issue 43 (28th October 2022) - Yang, Qiwei; Bai, Xu; Bao, Han; Li, Yukang; Men, Wanfu; Lv, Ling; Liu, Zhenghua; Han, Xiangjun; Li, Wenya
Abstract : Rationale: Postoperative chylothorax is a rare complication after pulmonary resection. Thoracic duct variations may play a key role in postoperative chylothorax occurrence and make treatment difficult. No studies in the literature have reported the successful treatment of chylothorax second to thoracic duct variation by lipiodol-based lymphangiography. Patient concerns: A 63-year-old male and a 28-year-old female with primary lung adenocarcinoma were treated by video-assisted thoracoscopic cancer resection, and suffered postoperative chylothorax. Conservative treatment was ineffective, including nil per os, persistent thoracic drainage, fatty food restriction, and somatostatin administration. Diagnosis: Postoperative chylothorax. Interventions: Patients received lipiodol-based lymphangiography under fluoroscopic guidance. Iatrogenic injuries were identified at thoracic duct variations, including an additional channel in case 1 and the lymphatic plexus instead of the thoracic duct in case 2. Outcomes: Thoracic duct variations were identified by lipiodol-based lymphangiography, and postoperative chylothorax was successfully treated by lipiodol embolizing effect. Lessons: Thoracic duct variations should be considered after the failure of conservative treatment for postoperative chylothorax secondary to pulmonary resection. Lipiodol-based lymphangiography is valuable for identifying the thoracic duct variations and embolizing chylous leakage.